The stonecutter [compact disc, unabridged] - Läckberg, Camilla, 1974- (HighBridge Audio, 2012)
The remote resort of Fjällbacka has seen its share of tragedy, though perhaps none worse than that of the little girl found in a fisherman's net. But the post-mortem reveals that this is no accidental drowning. Local detective Patrik Hedstrõm has just become a father. It is his grim task to discover who could be behind the methodical murder of a child both he and his partner, Erica, knew well. He knows the solution lies with finding the reason for such a terrible crime. What he does not know is how this case will reach into the dark heart of Fjällbacka and tear aside its idyllic façade, perhaps forever.